Mutational analysis of sequences downstream of the TATA box of the herpes simplex virus type 1 major capsid protein (VP5/UL19) promoter. - Huang, C J (1993)
Transient expression assays with the herpes simplex virus type 1 (HSV-1) promoter/leader controlling the beta gamma (leaky-late) VP5 (UL19) mRNA encoding the major capsid protein showed that no more than 36 to 72 bases of VP5 leader are required for full-level expression. Constructs lacking the viral leader and the transcription initiation site expressed the reporter gene at about 20% of the maximum level. We confirmed this observation by using recombinant viruses in which VP5 promoter/leader deletions controlling the bacterial beta-galactosidase gene were inserted into the nonessential glycoprotein C (UL44) locus of the genome. Sequences within +36 are required for full-level expression, and removal of all leader sequences including the cap site resulted in a 10-fold decrease in reporter mRNA accumulation. The removal of the leader sequence had a measurable effect upon the kinetics of reporter mRNA accumulation, but insertion of the entire VP5 leader and cap site into a construct in which the reporter gene was controlled by the kinetically early (beta) dUTPase (UL50) promoter did not result in any significant change in the kinetics of dUTPase promoter expression. These results suggest that DNA sequences both 5' and 3' of the TATA box are important determinants of the beta gamma kinetics and levels of VP5 mRNA accumulation in the infected cell.